Cost overrun of construction project in Pahang : causes and solution - Nurafiqah, Abu Hasan (2017)
The construction industry plays a vital role in developing the country’s infrastructure and was consider a pre-requisite for high levels of economic growth. Most of Project manager will reassure client that the construction project will be completed within budgetary cost and on time. However, most construction projects experience cost overrun and it put massive financial burden on the client or project owner. Cost overrun occurs when the final cost of the construction at the end of completion exceeded the original contract value. Therefore this research was carried out to identify the most influence factors in cost overruns and to analyze possible solutions to minimize or control cost overruns. The study is based on a literature review investigating causes and solution of cost overruns as well as a survey that was conducted among professionals in the construction industry in Pahang. A total of 30 filled questionnaires were collected from clients, consultants and contractors. The respondents were asked to rate the listed causes and solution on the basis of probability of occurrence and severity of impact. Relative Important Index (RII) analysis was used to analyze the data collected and to rank the most influence factor of cost overrun and the best possible solution of cost overrun. From the analysis of the result it found that the most influence factor of cost overrun is error in cost estimation and the most significant solution of cost overrun is select a suitable contractor not only on the basis of price and time offerings, but also on experience, financial standing, capacity and expertise. Based on the key findings of the research, it was recommended that each construction players in construction industry need to understand the factors that influence cost overrun in each stage of the life cycle of the projects and take a necessary precaution to avoid this problem. For instance, contractors are recommended to have qualified technical staff with appropriate experience of the project, owners are advised not to depend on the lowest price contractor to execute the project and consultants are recommended to continuously coordinating activities and supervising to provide guidance, and discipline as required so they are performed in accordance with their importance with a minimum of conflict.